Pendampingan UMKM di Wilayah Tangerang Selatan Sektor Food and Beveraged Dalam Pembuatan Perizinan Usaha Mikro Kecil (UMK) Melalui Online Single Submission (OSS) Berbasis Risiko - Rinaldo, Rinaldo; Jamilah, Siti; Windiani, Arovah; Adrian, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
Having a Business Identification Number and its management is carried out electronically, the aim is to guarantee the legality of a business, increase opportunities for; business, get training, take part in government procurement of goods/services, certify halal product guarantees, and SNI certificate for UMK development, or in other words to get a sign of business ownership and make it easier to run a business. The socialization of making NIB is a collaboration between UMJ and the owner of C. DOFF COFFEE as a form of community service. In the form of counseling and assistance regarding the importance of obtaining permits. The output that is being processed is to publish the results of this activity in the Jurnal Pengabdian Masyarakat Nusantara.